(untitled) (Research, Society and Development, 2021)
Objective: To understand the actions of Nurses in the management of cancer patients undergoing chemotherapy and their impacts. Methodology: This is an integrative review study, carried out in six stages, with a quantitative approach. Studies on the actions of Nurses in the management of patients undergoing chemotherapy treatment were listed in the Brazilian context. The time frame covered studies from the period 2016 to 2020, in English, Portuguese and Spanish. Results: 17 studies were selected, which presented the following thematic groups: 1) Actions performed by Nurses in the management of patients undergoing chemotherapy and; 2) Impacts generated by the referred actions. With regard to the actions carried out, it was possible to identify that they occur beyond assistance, with actions in health management and education being evidenced, including in the form of technological productions that were widely demonstrated in studies, with emphasis on the preparation of manuals, protocols and teaching materials. Regarding the impacts generated by the actions of Nurses, the following elements were highlighted in the studies: promoting access to health education; relieving the patient’s stress load and providing care individually. Conclusion: It was possible to highlight the various actions of nurses at all times in the chemotherapy process, going beyond the scope of care, demonstrating the importance of such a professional category in that context. In addition, it was evidenced that nurses routinely use the development of new technologies to improve professional processes, generating positive impacts and contributing directly to improving the management of cancer patients.